Penetapan Biaya Standar Sebagai Pengendalian Biaya Produksi Pada Avos Coffee And Resto Medan - Zega, Magdalena; Daulay, Zulia Rifda (Jurnal Ekonomi, Akutansi dan Manajemen Nusantara, 2024)
Avos Coffee and Resto Medan produces 1,000 cups of coffee every day with a predetermined sales target. However, this target is difficult to achieve and uncontrolled production costs can reduce profits, so control is needed. The aim of this research is to analyze the application of standard costs to control production costs at Avos Coffee and Resto Medan. This research is a descriptive qualitative research using data on actual production costs and standard production costs with one difference model deviation analysis calculations. Data collection techniques using observation, interviews and documentation. The results of this research show that the implementation of standard costs that has been carried out at Avos Coffee and Resto Medan is not optimal, this is because the main indicators are raw material costs, direct labor costs and factory overhead costs which are quite optimal. However, there were adverse deviations in raw material costs caused by price increases in December, causing them to be less than optimal, while direct labor costs and factory overhead costs were in a fairly optimal condition. Even though it is not optimal and there are many obstacles experienced, Avos Coffee and Resto Medan is able to maintain its business and continue producing. So by implementing these standard costs, Avos Coffee and Resto Medan can maintain its consistency and become better in the future.